Thinking About the Mental Health of Chinese-Costa Rican People: Historical Alterities and Sociocultural Adaptation - Pandolfi Zamora, Wilberth (2025)
The aim of this paper is to reflect, from a decolonial sociological approach, on the dynamics of sociocultural adaptation involved in the migratory processes experienced by the sons and daughters of Chinese people in Costa Rica, and the influence of this process on their mental health. Here it highlights key elements of this adaptation process crossed by multiple violence dynamics such as racialization and xenophobia towards the Chinese and Chinese-descendant population in Costa Rica, which is experienced by these people daily, in various spaces and institutions where inequalities and structural violence are condensed individually and collectively.